PHILOSOPHICAL AND ANTHROPOLOGICAL FOUNDATION OF MODERN PEDAGOGICAL EDUCATION (Academicia Globe: Inderscience Research, 2021)
The article describes the tendency for the integration of pedagogical concepts of education on a philosophical and anthropological basis, the philosophical and anthropological approach presupposes a certain method of studying education - “philosophizing”, which is directly related to the study of a person, his life, his personality, the search for means of assisting him in self-determination, finding the meaning of life.